EXTH-85. TARGETING CLAUDIN 6 WITH CAR T CELL THERAPY FOR ATYPICAL TERATOID/RHABDOID TUMOR. (14th November 2022) - Madsen, Peter; Stern, Allison; Griffin, Crystal; Oehm, Petra; Rengstl, Benjamin; Flemming, Carina; Resnick, Adam C; Storm, Philip B; Foster, Jessica
Abstract: Atypical teratoid/rhabdoid tumor (ATRT) is an aggressive brain tumor that predominantly affects young children and has an average 5-year survival under 50%. Novel, targeted therapies are desperately needed. Claudin 6 (CLDN6) is a tight junction protein present during development and expressed in up to 70% of ATRT specimens but not in normal tissue, making it a promising immunotherapeutic target. CLDN6-targeted chimeric antigen receptor (CAR) T cells in combination with a CAR T cell–amplifying mRNA vaccine have demonstrated antitumor activity against other CLDN6-expressing cancers in pre-clinical and phase I adult trial (NCT04503278; Haanen J et al AACR, 2022). To assess the effectiveness of CLDN6-targeted CAR T cells against ATRT, we utilized a second-generation mRNA CAR with a 4-1BB costimulatory domain and single-chain variable fragment against CLDN6 (Reinhard et al, 2020). Patient-derived ATRT specimens were assessed by RNAseq for CLDN6 expression (mean FPKM= 11.4) and by immunohistochemistry (positive staining in 53% of specimens). Tumor-derived cell lines were validated for CLDN6 expression by flow cytometry. Co-culture of CLDN6-directed mRNA CAR T cells with ATRT cell line 7316-2187 resulted in tumor-specific cytotoxicity compared to CD19-directed control CAR T cells (92% versus 15% at 10:1, p< 0.0001; 86% versus 0% at 5:1, p< 0.0001). Similar results were seen with ATRT cell line 7316-2141 (75% versus 7% at 10:1, p< 0.0001; 53% versus 0% at 5:1, p< 0.0001). Both CLDN6- and CD19-directed CAR T cells showed no cytotoxicity against CLDN6-negative cell line 7316-4149. Patient-derived xenograft models were also created through intracranial injection of multiple ATRT patient cell lines, and ongoing work will evaluate locoregional administration of CLDN6-directed CAR T cells in orthotopic xenograft models to test in vivo efficacy. This work highlights the potential for targeting CLDN6 via CAR T cell therapy in patients with ATRT as a novel therapeutic strategy for these devastating tumors.